Rancang Bangun Aplikasi Bon Permintaan Dan Pengeluaran Barang Menggunakan Metode Prototype Berbasis Website - Athaya, Aielsa Naomi; Marpaung, Noveri Lysbetti (Jurnal Informatika: Jurnal Pengembangan IT, 2023)
Goods purchase requisitions and goods issue documents are receipts for purchase requisitions and goods issues for distribution goods from the unit of work to the warehouse. pt. Perkebunan Nusantara V still uses the manual method of registering and approving the Goods Request Form using a form filled out by a factory assistant and signed by multiple parties. Therefore, it takes 5-30 business days to collect all signatures. If all parties are present, the product request notification can be signed and approved immediately. However, if this is not the case, the bill of goods approval process will be delayed. For this reason, urgent needs often result in goods being released from the warehouse before the invoice has been fully approved. Therefore, there is a need for an application that helps companies manage good purchase requisitions from warehouses. The application is implemented as a website that allows users to approve notes step-by-step online. The prototyping method allows developers to design and build systems more efficiently because discussions take place between users and developers during the system development process. PHP Laravel is used as programming language and MySQL as database. The tests for this application are based on the ISO 9126 test standard and give the following results: According to the USE survey, functionality scored 100%, reliability scored A, usability scored 90.07 across the four factors, efficiency scored B, performance score 88%, The structural score was 87%. Maintainability was evaluated as A grade with a debt ratio of 2.6%, and portability was evaluated as 100%. This application reduced the approval time to less than 5 hours and test results showed that the application works well and is suitable for enterprise use